До рая подать рукой: Роман: перевод с английского / Д. Кунц - Кунц Д. (Persona grata, 2002)
Экземпляры: аб. (2009) / Инвентарный номер: 52702 / Цена: / Сис.шифр: 84(7Сое)-4 / Авт.знак: К 91 / ГРНТИ: 17.82.31 / ББК: 84(7Сое)-44